‘Exotic Eroticism’: Gwendolen Harleth and Daniel Deronda - Julia Kuehn (Cahiers Victoriens et Edouardiens)
The essay looks once more at the relationship between the two protagonists of George Eliot's final novel. It argues that rather than through issues of class, as scholars have conventionally argued, Gwendolen Harleth's interest in Daniel Deronda must be understood through the ethnic otherness he represents. He is, as the first chapter construes it so unmistakably, ‘different' from the men this young Englishwoman normally socialises with, and the enquiry into Deronda's origins and heritage is pursued alongside questions of his perceived ‘un-Englishness’. The essay introduces the paradigm of ‘the exotic erotic’—adapted from Judith Butler's Bodies that Matter—to explore Gwendolen Harleth's simultaneous racialising and sexualising of Daniel Deronda. A brief overview of recent postcolonial reassessments of the concept of ‘exoticism’, and of Butler's reinterpretation into the context of gender studies, precedes the close reading of the literary text.